Design of Underactuated Manipulator based on Metamorphic Theory - Jialei Bao; Kang Han; Chengpu Zheng; Yu'nan Cao; Kai Sun (Jixie chuandong)
A new structure of underactuated manipulator is proposed to meet the need of multi-functional end fixture of robot. The most innovative point of the manipulator is that its end knuckle is completely passive envelope， which improves the grasping stability. The grasping attitude analysis and stability analysis are carried out， the feasibility of the scheme is verified， and the grasping attitude of different objects is verified. The prospect of the control strategy research is put forward.